Communicators and Innovators in Research and Development Organizations - Keller, Robert T.; Holland, Winford E. (Academy of Management Journal, 1983)
The article discusses research pertaining to the personal characteristics of communicators and innovators in research and development (R&D) organizations. Preliminary results suggested an overlap between the roles of communicator and innovator in the organizations studied. The results indicated that innovators/communicators had a low need for clarity, a high level of education, and high self-esteem. In addition the study found that physical propinquity was associated with the strong formation of components among innovators, communicators, and other professional employees.